2006
DOI: 10.1016/j.ejheart.2006.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Presence and development of atrial fibrillation in chronic heart failure

Abstract: Background: Atrial fibrillation is common in heart failure, but data regarding beta-blockade in these patients and its ability to prevent new occurrence of atrial fibrillation are scarce. Methods: Baseline ECGs in MERIT-HF were coded regarding baseline rhythm, and outcome was analyzed in relation to rhythm. Occurrence of atrial fibrillation during follow-up was also analyzed. Results: At baseline atrial fibrillation was diagnosed in 556patients (13.9%). Mean metoprolol CR/XL dose in patients in atrial fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 36 publications
3
51
1
2
Order By: Relevance
“…Apparently, a resting heart rate below 110 beats per minute was low enough to prevent an increased number of hospitalisations for heart failure. This is in line with the notion that beta-blockers do not improve the prognosis of patients with heart failure who have atrial fibrillation [41,42].…”
Section: Failure Of Strict Rate Control and Outcomesupporting
confidence: 73%
“…Apparently, a resting heart rate below 110 beats per minute was low enough to prevent an increased number of hospitalisations for heart failure. This is in line with the notion that beta-blockers do not improve the prognosis of patients with heart failure who have atrial fibrillation [41,42].…”
Section: Failure Of Strict Rate Control and Outcomesupporting
confidence: 73%
“…8 Then again, a retrospective analysis of the MERIT-HF study did not detect an effect of treatment with metoprolol succinate on mortality in the subset of CHF patients with atrial fibrillation. 49 Finally, it has been reported that carvedilol may be preferable to metoprolol tartrate to prevent the development of renal failure in patients with CHF. 50 These studies, however, included few patients, and in some studies follow-up was short.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, beneficial effects of b-blockers on outcome in patients with heart failure and AF have never been prospectively studied. Retrospective analyses of large-outcome studies suggested significant benefits of treatment with carvedilol [13] and formally not with bisoprolol [19] or metoprolol [20]. On the other hand, a retrospective study in patients with heart failure observed an association of the Arg389Arg (plus Gln27/X for the b2-adrenoceptor) genotype with a twofold higher mortality risk in patients treated with carvedilol, but not with metoprolol [21].…”
Section: Practical Consequences?mentioning
confidence: 99%